Monte Carlo Simulation of the Effective Solid Angle and the HPGe Response to Different Mono-Energetic Protons from Extended Source - Kadhim, Alaa (Iraqi Journal of Science, 2023)
A program using Mont Carlo techniques has been written to calculate the effective solid angle of the detection system and simulate the response of the HPGe to mono-energetic protons from an extend source. It has been found that the fraction of the protons which leave through the cylindrical surface and deposit only part of their kinetic energy in the crystal increases with proton energy and the consequent increase in their range.